Resenha: The Routledge Handbook of the Archaeology of Indigenous-Colonial Interaction in the Americas. PANICH, Lee M.; GONZALEZ, Sara L. (eds.), 2021. - Peixoto, Sílvia Alves (Cadernos do LEPAARQ (UFPEL), 2022)
PANICH, Lee M.; GONZALEZ, Sara L. (eds.). The Routledge Handbook of the Archaeology of Indigenous-Colonial Interaction in the Americas. London and New York: Routledge Taylor & Francis Group, 2021. 578p.